(untitled) (Malaysian Journal of Learning and Instruction, 2017)
Purpose – This qualitative study explores if there were any changes in teachers’ reflection in terms of content and levels after participating in five lesson study cycles. Method – Case study method was employed in this study. Six mathematics teachers from a primary school participated in this study. They set up a lesson study group and conducted five lesson study cycles. In each lesson study cycle, the lesson study team members plan, teach and observe a research lesson. Qualitative data was collected through participatory observation, reflection sessions, collection of artefacts and interviews. Findings – Analysis of data revealed that there were some slight and slow changes in the teachers’ reflection as they progressed from the first to the fifth reflection sessions. These changes included: (1) teachers’ reflection became more specific and in-depth; (2) teachers’ reflection about the pupils’ learning became more in-depth; (3) teachers reflected from pupils’ perspectives; and (4) teachers reflect athigher level of reflection. Significance – The study revealed that the criteria of lesson study, collaborative and classroom observation, made it feasible in promoting teachers’ reflection. The educators could employ lesson study as an approach to promote teachers’ reflection. However, the effectiveness of lesson study in promoting teachers’ reflection is 146 Malaysian Journal of Learning and Instruction: Special Issues 2017: 145-172 affected by the number of lesson study cycles being carried out and the presence of the knowledgeable others.